Imaging Cardiac Developmental Malformations in the Mouse Embryo - Mohun, T; Weninger, W; Bhattacharya, S (Elsevier, 2010)
This chapter discusses imaging cardiac developmental malfunctions in the mouse embryo. Studies of human genetic architecture cannot provide a mechanistic understanding of gene function in cardiac development, and analysis of gene-gene and gene-environment interactions in humans remains a challenge. These considerations necessitate the use of animal models, the most appropriate and widely used being the mouse. Like the human, the mouse has a four-chambered heart with a septated outflow tract, left-sided great arteries, and parallel pulmonary and systemic circulations. Common cardiac malformations such as septal, outflow tract, and aortic arch and pulmonary trunk defects can thus be identified in mouse embryos, and mouse mutations typically recapitulate the cardiac malformations observed in patients with mutations in the same genes (reviewed in Schneider and Bhattacharya, 2004). Imaging such a complex and dynamic structure as the developing heart plays a crucial role in such studies, underlying accurate assessment of phenotype. New anatomical imaging techniques such as optical projection tomography, high resolution episcopic microscopy and magnetic resonance imaging provide ways to supplement conventional histology with comprehensive image data, yielding three-dimensional models that allow systematic, quantitative comparisons of structure. These imaging methods have complementary strengths, and by combining them it is possible to envisage a powerful cardiac phenotyping pipeline. © 2010 Elsevier Inc. All rights reserved.